CORRELATION BETWEEN LBW HISTORY AND STUNTING INCIDENCE: A LITERATURE REVIEW - Ramadhan, Sherina; Amalia , Rize Budi; Sudaryanti , Lestari (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Indonesia is facing a significant nutrition problem characterized by a high prevalence of undernutrition cases. Malnutrition is a consequence of poor nutritional status. Stunting is one form of malnutrition associated with a history of inadequate nutrient intake, making it a chronic nutritional problem. One potential factor affecting child growth is a history of low birth weight (LBW). The study aims to analyze the correlation between a history of LBW (Low Birth Weight) and the occurrence of stunting. Method: This research used a literature review study design, using secondary data sourced from electronic databases, consisting of 111 Pubmed articles, 518 Google Scholar articles, and 138 Science Direct articles. Article searches were conducted using keywords related to low birth weight for gestational age, stunting, and children, resulting in 15 relevant articles. The searches using these keywords are limited ( the last 10 years) and then screened according to inclusion and exclusion criteria. Result: Twelve of fifteen pieces of literature reinforce each other by finding low birth weight has a correlation with the occurrence of stunting. While some studies have confirmed a significant correlation between LBW and stunting, other studies have not found any such link. This suggests that the relationship between LBW and stunting is intricate, and there may be other factors that contribute to the occurrence of stunting. Conclusion: A history of LBW (Low Birth Weight) is a contributing factor in the occurrence of stunting in children.